Black rice addition prompted the beer quality by the extrusion as pretreatment. Issue 11 (27th September 2019) - Zhang, Tianyu; Zhang, Haijing; Yang, Zhe; Wang, Yiran; Li, Hongjun
Abstract: Flavor compounds, including total polyphenols, amino acids, and protein, in beer with extruded black rice as adjunct were detected and analyzed. Beer brewing technique has been intensively investigated in the past century. The chase of beer quality, including the color, flavor, foam, nutrition, and functionality, attracted considerable attention. Hence, headspace solid‐phase microextraction in combination with a gas chromatography coupled to mass spectrometry (HS‐SPME‐GC–MS) was used to analyze flavor compounds qualitatively and quantitatively. A total of one organic acid, one aromatic, ten alcohols and 23 esters were present in extruded black rice adjunct beer. Protein components and molecular weight were analyzed, and the results were consistent with those of traditional beer in terms of content of foam‐stabilizing protein. The contents of essential amino acid which is an important nutritive index were higher than those in traditional rice adjunct beer, especially valine (70.9 mg/L) and threonine (42.8 mg/L). The representative ingredients of extruded black rice adjunct beer were polyphenols, nerolidol, geraniol, and geranylgeraniol which affected the functionality and antioxidant ability. Abstract : A new attempt: extruded black rice as adjunction beer